2015
DOI: 10.3109/08941939.2015.1005780
|View full text |Cite
|
Sign up to set email alerts
|

Schlafen 3 Mediates the Differentiating Effects of Cdx2 in Rat IEC-Cdx2L1 Enterocytes

Abstract: Aim Mature, differentiated enterocytes are essential for normal gut function and critical to recovery from pathological conditions. Little is known about the factors that regulate intestinal epithelial cell differentiation in the adult intestine. The transcription factor, Cdx2, involved in enterocytic differentiation, remains expressed in the adult. Since we have implicated Slfn3 in differentiation in vivo and in vitro, we examined whether it also mediated differentiation in the IEC-Cdx2-L1 cell model of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Indeed, Schlafen 3 is required for the induction of villin expression by the differentiating transcription factor Cdx2 in rat IEC-6-Cdx2-L1 cells. [50]. Thus, there may be good reason to link Schlafen 3 to rodent enterocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Schlafen 3 is required for the induction of villin expression by the differentiating transcription factor Cdx2 in rat IEC-6-Cdx2-L1 cells. [50]. Thus, there may be good reason to link Schlafen 3 to rodent enterocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no significant differences between male Slfn3KO and WT mice and no significant differences in Notch1 expression for either sex between Slfn3KO and WT mice (Fig 8A and 8B). Additionally, since we have shown that Slfn3 can affect the expression of Cdx2 in IEC-6 cells and Boyd et al listed Notch2 as a target gene of Cdx2 [1, 31] we explored whether the expression of Cdx2 was affected in Slfn3KO mice. In agreement with the Notch2 expression, Cdx2 was also increased in Slfn3KO female mice in comparison to WT females, while there was no significant change between the male genotypes (Fig 8C).…”
Section: Resultsmentioning
confidence: 99%
“…Slfn3 is expressed preferentially in CD4 + CD25 + Treg cells and downregulates during T cell activation by TGF-β [ 42 ]. Outside the immune system, Slfn3 also regulates enterocytic differentiation [ 28 , 43 , 44 ] and colonic mucosal growth during aging [ 45 ]. Slfn3 knockout mice show gender-specific differences in weight gain, intestinal epithelial differentiation, and impaired enterocyte differentiation after bowel resection [ 46 ].…”
Section: Role Of Schlafens In Non-malignant Biologymentioning
confidence: 99%